Evaluation of bone mineral density and its influencing factors in patients infected with HIV under antiretroviral therapy - Alireza Azarboo; Mahboobeh Hemmatabadi; Noushin Fahimfar; Zahra Faghihi; SeyedAhmad SeyedAlinaghi; Nooshin Shirzad; Ladan Abbasian (BMC Infectious Diseases)
Abstract Background Reduced Bone Mineral Density (BMD) has been linked to Human Immunodeficiency Virus (HIV) infection and treatment. There is a lack of information regarding the osteoporosis status of middle-aged patients with HIV in Iran, despite the fact that Antiretroviral Therapy (ART) is widely accessible. Objective The purpose of this cross-sectional study was to assess the BMD status and low BMD risk factors in patients with HIV under ART living in Iran. Methods Data were collected from individuals diagnosed with HIV aged 30–50, receiving ART for at least 6 months. Dual-energy X-ray absorptiometry scans assessed BMD in femoral neck, total hip, and lumbar regions. Pearson’s correlation coefficients identified relationships between BMD and demographic and laboratory predictors. Univariable and multivariable logistic regression models assessed predictors of low lumbar BMD. Results Among 80 HIV-infected individuals (mean age: 41.1 ± 5.6 years, 60.4% male), 15% exhibited low BMD in the lumbar spine and 3.75% in the femoral neck. Serum phosphate levels were negatively correlated with BMD across the femoral neck, total hip, and lumbar regions (e.g., lumbar BMD: r = -0.24, p = 0.03). Parathyroid hormone (PTH) showed negative correlations with femoral neck and total hip BMD (r = -0.26, p = 0.01; r = -0.29, p = 0.01, respectively). Estradiol positively correlated with lumbar BMD in females (r = 0.36, p = 0.04), and BMI positively correlated with BMD in all regions (e.g., lumbar: r = 0.41, p = 0.001). Testosterone was inversely associated with the odds of lumbar low BMD (OR [95% CI] = 0.79 [0.62–0.96], p = 0.02). Duration of HIV or treatment, CD4 levels, and viral load were not significantly associated with BMD. Conclusion This study highlights the multifactorial nature of BMD changes in individuals living with HIV. By identifying correlations between metabolic, hormonal, and disease-related factors and bone health, our findings bring attention to an often-overlooked aspect of HIV management, that is patients with HIV may benefit from routine BMD screening, as it could help identify early risks of low BMD.